Detection of Foodborne Pathogens Through Volatile Organic Compounds Sensing via Metal Oxide Gas Sensors - Shiv Dutta Lawaniya; Anjali Awasthi; Prashanth W. Menezes; Kamlendra Awasthi (Advanced Sensor Research)
Abstract Foodborne pathogens are a crucial diagnostic target for the food, beverage, and healthcare sectors due to their ubiquity and the potential damage they may do to the public's well‐being, food safety, and the economy. Over the past few decades, there has been an increased focus on developing highly precise and trusted biosensors in an effort to eliminate the discrepancy between reporting demands and currently used traditional detection approaches. Metal oxide semiconductor (MOS)‐based gas sensors have rapidly advanced in recent years, becoming a dominating technology for developing devices in food‐quality management, biomedical research, and diagnostics. This review systematically explores recent advancements in gas sensing technologies utilizing metal oxide‐based sensors for the detection of foodborne pathogens through the analysis of volatile organic compounds (VOCs). The comprehensive discussion encompasses insights into various foodborne pathogens, their implications for human health, diverse metal oxide characteristics, strategies for enhancing their sensing capabilities, and the distinctive features of VOCs. Furthermore, a thorough examination of the utilization of different metal oxides in VOC sensing is provided, addressing both existing challenges and potential future developments. In summary, employing gas sensing techniques for foodborne pathogen detection holds substantial commercial promise compared to alternative bio‐sensing approaches.